Students' Critical Thinking Skills on Motion System Material in Elementary School - Putri, Febrialita Salma Dwinandha; Paramitha, Sandey Tantra; Anggraeni, Leni (KnE Social Sciences, 2024)
Scientific thinking skills are a key to learning science. The current research aims to analyze: (1) if the design of the Learning Implementation Plan (RPP) contains indicators of students’ critical thinking skills and (2) class IV learning activities leading to critical thinking skills. The research is qualitative. The research samples used were fifth-grade teachers and students of classes IVA and IVB. The research object used is the RPP and the science learning activities. Data collection techniques were interviews, observation, and documentation. The instruments used in the study were interview sheets and observation sheets validated through content and construct validity tests. The results showed that: (1) the design of the RPP leads to indicators of critical thinking skills and (2) it can be implemented through the learning process. Keywords: movement system, learning, elementary school